Schools as Racial Spaces: Understanding and Revisiting Structural Racism - Blaisdell, Benjamin (My University, 2015)
This presentation was the invited paper presentation for the College of Education Faculty and Student Research Showcase during the Research and Creative Achievement Week in 2015.
Keywords: Schools; Racial literacy; Racial spaces; Racism